2016
DOI: 10.1530/jme-16-0052
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome landmarks of the functional maturity of rat beta-cells, from lactation to adulthood

Abstract: Research on the postnatal development of pancreatic beta-cells has become an important subject in recent years. Understanding the mechanisms that govern beta-cell postnatal maturation could bring new opportunities to therapeutic approaches for diabetes. The weaning period consists of a critical postnatal window for structural and physiologic maturation of rat beta-cells. To investigate transcriptome changes involved in the maturation of beta-cells neighboring this period, we performed microarray analysis in fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…Our results showed that, distinct to other isoforms, Cav3.2 expression progressively increased from one stage of maturation to the other. This confirms the validation approach of our group, whose microarray analysis revealed a higher expression of different calcium channel isoforms, like α1H subunit (Cav3.2), in adult beta cells compared with P20 cells ( 20 ). Neurons and myocytes also exhibit a variable pattern of calcium channel expression during different stages of development ( 42 44 ).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our results showed that, distinct to other isoforms, Cav3.2 expression progressively increased from one stage of maturation to the other. This confirms the validation approach of our group, whose microarray analysis revealed a higher expression of different calcium channel isoforms, like α1H subunit (Cav3.2), in adult beta cells compared with P20 cells ( 20 ). Neurons and myocytes also exhibit a variable pattern of calcium channel expression during different stages of development ( 42 44 ).…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, a recent work of our group revealed that transcriptome changes are involved in the beta-cell maturation, by microarray analysis ( 20 ). We showed a differential expression in P20 and adult cells in a variety of gene sets including those involved in excitability.…”
Section: Introductionmentioning
confidence: 99%
“…Immediately after birth, β-cells are not fully functional and have to undergo a major gene reprogramming to acquire the ability to secrete adequate amounts of insulin in response to glucose (1). Our group and others (2,5,24) have shown a large-scale rewiring of transcriptional programs occurring during the neonatal period. However, little is known on cis-regulation of gene expression at the chromatin level before and after weaning.…”
Section: Discussionmentioning
confidence: 82%
“…Cells that generate and secrete insulin can be produced in vitro using various methods (3,4) and are similar to β-cells in many aspects. However, these cells show lower glucose-stimulated insulin secretion (GSIS) and transcriptome differences compared with normal β-cells (5). Consequently, there is a need to better understand the regulation of the maturation process to enable the engineering of fully functional surrogate insulin-producing cells.…”
Section: Introductionmentioning
confidence: 99%
“…We are interested in the physiological changes during early postnatal development, specifically around weaning in Wistar rats (that under laboratory conditions occurs at postnatal day 20 (p20)). During this critical developmental window, which lasts approximately eight days, previous works by Hiriart and collaborators identified changes related to the functional maturation of pancreatic beta cells [ 22 , 24 26 ] and observed systemic IR in male p20 rats [ 22 ].…”
Section: Introductionmentioning
confidence: 99%